DEVELOPMENT OF BRANCH SYSTEM OF CERTIFICATION OF SOFTWARE AND INFORMATION MEANS OF SCIENTIFIC AND EDUCATIONAL PURPOSE - Sergeev, О.Ю. (Journal of Information Technologies in Education (ITE), 2010)
The article describes the development and implementation of regulatory, organizational, scientific methods of industry certification, the concept of creating software and tools support certification.